Correlation analysis of osteoporosis and vertebral endplate defects using CT and MRI imaging: a retrospective cross-sectional study - Hao, Song; Yuxiao, Luo; Huilan, Li; Jun, Hua; Dong, Liu (Frontiers in Physiology, 2025)
BackgroundOsteoporosis (OP) and vertebral endplate defects are important manifestations of vertebral degenerative changes that greatly affect the quality of life of elderly people. This study investigated the potential association between vertebral endplate defects and osteoporosis using imaging modalities.MethodsComputed tomography (CT), magnetic resonance imaging (MRI), bone mineral density (BMD) and other relevant imaging data, as well as age, sex, body mass index (BMI), and degree of low back pain data, were retrospectively analysed. The vertebral Hounsfield unit (HU) value and the maximum width and maximum depth of the vertebral endplate defect were measured and standardized. A HU <110 was defined as OP. Logistic regression was used to identify the risk factors for vertebral endplate defects.ResultsDemographic data from a total of 199 patients were included in this study, along with data from 995 vertebral bodies. The relationships between the HU value and other data between the vertebral body defect group and the nonvertebral body defect group were compared. We found significant differences in age (70.6 ± 8.4 vs. 63.8 ± 9.5, p < 0.001), sex (male/female) (26/69 vs. 43/61, p < 0.05), BMI (23.8 ± 3.4 vs. 24.8 ± 3.4, p < 0.05), and total spine HUs (84.65 ± 35.49 vs. 124.86 ± 49.59, p < 0.001). The lower HU group had larger endplate defects (p < 0.001, p < 0.01), and the lower endplates had a greater standardized defect width and cumulative defect score than the upper endplates (p < 0.01). There were statistically significant associations between endplate defects and age (OR = 1.0, p = 0.042) and total spine HUs (OR = 0.98, p = 0.001).ConclusionThere was a correlation between OP and the size of the vertebral endplate defect, and the defect size increased with decreasing bone mass. According to our results, vertebral endplate defects are more likely to occur in elderly individuals, females, and individuals with OP. With respect to the spinal structure, vertebral endplate defects are more likely to occur in the upper lumbar spine. Age and bone mass are the main factors associated with vertebral endplate defects.